Characteristics of Nanosize Spinel NixFe3-xO4 Prepared by Sol-Gel Method Using Egg White as Emulsifying Agent - Rudy Situmeang; Sukma Wibowo; Wasinton Simanjuntak; R. Supryanto; Rizki Amalia; Mitra Septanto; Posman Manurung; Simon Sembiring (Universitas Gadjah Mada, 2015)
In this study, sol-gel method using egg white as emulsifying agent was applied to prepare nano size spinel NixFe3-xO4 (with x = 0.2–1). Sample preparation was carried out by mixing the solution of Fe(NO3)3.9 H2O and Ni(NO3)3.6 H2O with egg white, and then the sample was stirred thoroughly using magnetic stirrer. After freeze–drying process, the sample was subjected to calcination treatment and subsequently characterized. The phase composition was evaluated using the X-ray diffraction (XRD) technique, followed by quantitative analysis using Rietveld and Debye-Scherrer Methods. The functionality of the sample was identified using Fourier Transform Infrared (FTIR) spectroscopy, and surface morphology and elemental composition were analyzed using scanning electron microscopycoupled with electron dispersive spectroscopy (SEM/EDS). The results of XRD characterization indicated that materials consist of various crystalline phases, with NiFe2O4 as a major phase. FTIR Analysis revealed the existence of both Lewis and Brønsted–Lowry acid sites, with Lewis acid as the prominent site. The sample was found to display relatively homogeneous surface morphology, having the crystallite size in the range of 33 to 61 nm according to the Debye-Scherrer equation. The EDS data indicated that the ratio of Fe/Ni is in agreement with the composition of the raw materials used.